Perceptions of the government's infant feeding guideline of urban poor mothers - Ferrer, Laila V. (2006)
The Philippine government issued Nutritional Guidelines for Filipinos in 1990 and a revised version in 2000. Although both documents contained an infant feeding guideline, the 1990 recommendation was for breast-feeding and weaning whereas the present (2000) edition is on exclusive breast-feeding and appropriate foods. This study was conducted to determine the perceptions of urban poor mothers on the present infant feeding guideline "Pasusuhin ang sanggol ng gatas ng ina lamang mula pagkasilang hanggang 6 na buwan at saka bigyan ng mga angkop na pagkain habang pinapasuso pa" (Breast-feed infants exclusively from birth to 6 months, and then, give appropriate foods while continuing breast-feeding) on the whole and in terms of its two key concepts- exclusive breast-feeding and appropriate foods. In addition, it also looked into the mothers' perceived benefits and barriers to exclusive breast-feeding, and addition of fats, oils and sugar to the diet of 6-11 month old infants. Three focus group discussions were conducted with each group having five to seven mothers. The questioning route was developed based on the objectives of the study, pre-tested and revised accordingly. A total of 18 mothers, 21-29 years of age and elementary school graduates participated in the discussions. The present infant feeding guideline advocates exclusive breast-feeding and giving appropriate foods. However, the mothers failed to see the connection between the two components and perceived the guideline as a recommendation to breast-feed infants for only six months. They were not in favor of exclusive breast-feeding because they considered it too restrictive and not feasible. The mothers considered several factors in their perception of benefits and barriers to exclusive breast-feeding, consistent with the findings of earlier local studies on breast-feeding. The benefits of exclusive breast-feeding were expressed in terms of its economic advantage, health of the child, bonding between mother and child and savings in time while the barriers were related to insufficiency of milk, mother's work and illness, and aesthetic considerations. The Complementary Feeding Guide has four concerns. On their part, the mothers were more interested in the kinds of foods appropriate for infants, age of introduction, method of preparation than the specified amounts of foods to be given. Contrary to the recommendations, they were of the opinion that complementary feeding should be given prior to six months and that it is not necessary to add fats, oils and sugar to the diet of infants. The mothers' perspective of infant feeding was broader compared to those who crafted the guideline. In addition to technical considerations, they took into account economic, aesthetic and social factors, and their day-to-day food-related practices. Contrary to the claim in the NGF 2000 handbook, the infant feeding guideline is not simple and easily comprehended. To enhance the understanding and acceptance of the guideline, the following measures are recommended: separation of the two component parts of the guideline; consistency of messages about infant feeding from government and private sources; and the teaching of the guideline starting with the familiar (breast-feeding) before introducing an unfamiliar concept (exclusive breast-feeding). Research is necessary to determine the effectiveness of the guideline.